Protection Of The Rights Of Customary Communities Towards The Use Of Natural Resources From A National Legal Perspective - Anis Noviya (PT. Anagata Sembagi Education, 2026)
Customary law communities are social entities that have existed long before the formation of the Indonesian state and have functional and cosmological relationships with natural resources in their customary territories. Article 18B paragraph (2) of the 1945 Constitution of the Republic of Indonesia recognizes and respects the existence of customary law communities and their traditional rights as long as they are alive and in accordance with the development of society and the principles of the Unitary State of the Republic of Indonesia. However, this constitutional recognition has not been fully implemented consistently in various sectoral laws and regulations governing the use of natural resources, resulting in overlapping regulations and legal uncertainty. This study aims to examine the form of recognition and legal protection of the rights of customary law communities to natural resources from a national legal perspective, as well as to analyze the challenges and effectiveness of such protection amidst the strong flow of investment and development. This study uses a normative juridical method with a legislative approach, a conceptual approach, and a case approach. The research results show that although the national legal framework, including Constitutional Court Decision Number 35/PUU-X/2012, has provided a strong foundation for the recognition of indigenous peoples' rights to customary forests and other natural resources, its implementation in the field still faces structural, procedural, and political obstacles, including the slow ratification of the Draft Law on Indigenous Peoples and the weak application of the principle of free, prior, and informed consent in the business licensing process in customary areas. This research recommends accelerating the formation of special laws on indigenous peoples, strengthening institutions at the regional level, and internalizing the principle of free consent into all licensing processes for the use of natural resources